Hubungan Pola Pengasuhan Dengan Kemandirian Anak Usia 5-6 Tahun di Panti Asuhan Sekacamatan Alang-Alang Lebar Palembang - Liana Azzachra; Nyimas Atika; Lidia Oktamarina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine whether there is an influence of parenting patterns on the independence of children in orphanages in Alang-alang lebar sub- district. The method used in this study is quantitative with a correlational research type. The population of this study was all children aged 5-6 years who lived in orphanages in Alang-alang lebar sub-district. The sample in this study was 20 children in orphanages in Alang-alang lebar sub-district with a random sampling method. Data collection techniques used were observation, questionnaires and documentation. After collecting the results of the questionnaire answers that had been distributed, the researcher processed the data using the SPSS Version 26 Program. The data analysis used was validity testing, reliability testing, simple linear regression, hypothesis testing and determination coefficient testing. After the analysis test was carried out, the calculated t > t table (8.956 > 2.093) and sig< 0.005 were obtained. Because the calculated t > t table, Ho was rejected and Ha was accepted, meaning that there was an influence of parenting patterns on the independence of children in the Alang-Alang Lebar Sub-district Orphanage.